Transit-timing variations in the AU Mic system observed with CHEOPS - Boldog, Á.; Davies, M.B.; Korth, J.; Zingales, T. (Astronomy and Astrophysics, 2025)
Context. AU Mic is a very active M dwarf star with an edge-on debris disk and two known transiting sub-Neptunes with a possible third planetary companion. The two transiting planets exhibit significant transit-timing variations (TTVs) that are caused by the gravi tational interaction between the bodies in the system. Aims. Using photometrical observations taken with the CHaracterizing ExOPlanet Satellite (CHEOPS), we aim to constrain the plan etary radii, the orbital distances, and the periods of AU Mic b and c. Furthermore, our goal is to determine the superperiod of the TTVs for AU Mic b and to update the transit ephemeris for both planets. Additionally, based on the perceived TTVs, we study the possible presence of a third planet in the system. Methods. We conducted ultra-high precision photometric observations with CHEOPS in 2022 and 2023. We used Allesfitter to fit the planetary transits and to constrain the planetary and orbital parameters. We combined our new measurements with results from previous years to determine the periods and amplitudes of the TTVs. We applied dynamical modelling based on TTV measurements from the 2018-2023 period to reconstruct the perceived variations. Results. We found that the orbital distances and periods for AU Mic b and c agree with the results from previous works. However, the values for the planetary radii deviate slightly from previous values, which we attribute to the effect of spots on the stellar surface. AU Mic c showed very strong TTVs, with transits that occurred ∼80 minutes later in 2023 than in 2021. Through a dynamical analysis of the system, we found that the observed TTVs can be explained by a third planet with an orbital period of ∼12.6 days and a mass of 0.2030.024+0.022 MO. We explored the orbital geometry of the system and found that AU Mic c has a misaligned retrograde orbit. The limited number of AU Mic observations prevented us from determining the exact dynamical configuration and planetary parameters. Further monitoring of the system with CHEOPS might help to improve these results. © The Authors 2025.
Keywords: Planets and satellites: fundamental parameters; Exoplanets; Interplanetary flight; Interplanetary spacecraft; Monolithic microwave integrated circuits; Orbits; Photometers; Planetary surface analysis; Satellites; Space debris; Tropics; Debris disk; Dwarf stars; Exo-planets; High-precision; Neptune; Orbitals; Timing variations; Transit timing; Ultra-high; Stars